1998
DOI: 10.1159/000020795
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Follow-Up of Hydronephrosis Detected by Prenatal Ultrasound: The Natural History

Abstract: Babies with hydronephrosis detected antenatally who were born at or referred to our hospital from 1990 to 1995 were followed up with ultrasound (U/S), micturating cystourethrogram (MCU) or nuclear medicine studies after birth. One hundred and three patients were diagnosed antenatally at 17–42 weeks gestation. Twelve cases were excluded from the analysis of the results because of incomplete data. Fifty-one (56%) patients had hydronephrosis without organic obstruction, and 80% of these became normal in 3 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 26 publications
2
24
0
4
Order By: Relevance
“…16 Three small prospective studies recognized that 10 to 30% of their ANH infants were lost to follow-up. 2,12,[17][18] More recently Lee et al, 3 in a meta-analysis (using a criteria similar to ours) noted that 246 (15%) of 1678 patients with ANH were lost to follow-up. Many investigators, however, have not mentioned any loss of patients in their ANH programs.…”
Section: Discussionsupporting
confidence: 52%
“…16 Three small prospective studies recognized that 10 to 30% of their ANH infants were lost to follow-up. 2,12,[17][18] More recently Lee et al, 3 in a meta-analysis (using a criteria similar to ours) noted that 246 (15%) of 1678 patients with ANH were lost to follow-up. Many investigators, however, have not mentioned any loss of patients in their ANH programs.…”
Section: Discussionsupporting
confidence: 52%
“…Alternatively, urinary tract dilatation might occur normally during urinary tract development, perhaps due to the occurrence of VUR before the formation of a competent flap-valve mechanism. In reviewing the long-term follow-up of antenatal urinary tract dilatation, there are always some cases where previously observed abnormalities are no longer detected in the postnatal period (14,25). Our data suggest that in wild-type mice, VUR resolves in the newborn period because the flap-valve mechanism has now become competent.…”
Section: Discussionmentioning
confidence: 60%
“…Urinary tract dilatation discovered on antenatal ultrasounds is not always detected on postnatal imaging (14,25). This raises many questions regarding its natural history, including the possibility that dilatation can occur as a transient finding during normal human embryogenesis (20).…”
Section: Hoxb7/ret Mice Have a High Incidence Of Vur Hoxb7/retmentioning
confidence: 99%
“…Five hundred and six potentially relevant studies were identified, of which 18 met the inclusion criteria (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Two studies reported overlapping patient cohorts but different outcomes (27,28).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The earliest reported fetal ultrasound was at 14 wk of gestation (21). Most studies reported that postnatal scans were not performed within 2 d after birth (17,20,22,23,(27)(28)(29)(30)(31), which may be important because newborns are initially oliguric and false-negative results are common at this time: 4 studies did not specify the earliest age at postnatal ultrasound assessment (18,29,30,33).…”
Section: Study Characteristicsmentioning
confidence: 99%